Exploring the relationship between family planning and intimate partner violence: a mixed-methods study - Iweka, Reuben O.; Sodje, Jedidiah D.; Anya, Chidinma J.; Nwaogwugwu, Joy C. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2025)
Background: Family planning is vital for reducing maternal morbidity and mortality, but in many developing countries, women’s access to it may be influenced or restricted by their partners due to prevailing gender norms. Given the inconsistent global and regional findings on the link between intimate partner violence (IPV) and family planning use, this study aims to examine their association within our local context. Method: A descriptive cross-sectional study using qualitative and quantitative methods was carried out with 421 women, their spouses, and healthcare providers at the family planning clinic of the University of Benin Teaching Hospital in Benin City, Nigeria. Quantitative data were analysed using statistical package for the social sciences (SPSS) 25.0, and p values of less than 0.05 were considered statistically significant. The qualitative data were analysed thematically. Result: The mean age group was 35.9±7.23, and the prevalence of IPV was 7.1%. Also, 92.6% reported that their husbands agreed with the chosen method of family planning, of which 87.2% did not require persuasion of their husbands before agreement. Of those whose husbands refused the family planning method, 19.4% attempted to convince their husbands, and 80.6% did not try to persuade them. About 30.0% experienced physical violence, 40.0% endured psychological violence, 13.3% faced sexual violence, and 16.7% experienced economic violence. The impact of family planning on IPV includes insomnia (73.3%), starvation (10.0%), suicidal ideation (10.0%) and body pain (6.7%). The qualitative analysis also showed cases of sexual, physical, and emotional IPV, especially from family planning. Conclusion: Although the occurrence of IPV was low among the study population, it showed that IPV affects family planning demand. This underscores the importance of enhancing family planning acceptance among couples by implementing couple counselling, increasing public awareness, empowering women, ensuring legal protection, and incorporating intimate partner violence (IPV) prevention into family planning services.